Exploring University Students’ Views on How Critical Thinking is Promoted in Focus Group Discussions - Dyah Supraba Lastari; Arjulayana Arjulayana (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: The purpose of this study is to examine students’ perceptions of the integration and development of critical thinking skills through Focus Group Discussions class in an English Education Study Program. Methodology: This study employed a mixed methods research design. Data were collected using a structured questionnaire survey and structured interview as research instruments. Quantitative data were analyzed using descriptive statiscal analysis in the form of index percentage score, while qualitative data were analyzed through thematic-analysis to identify patterns related to students’ perceptions of critical thinking development. Main Findings: The results of the study indicate consistently positive students’ perception, shown by high index percentage scores, that Focus Group Discussion activities effectively develop critical thinking skills which include analytical reasoning, evaluation of multiple perspectives, synthesis of ideas, and evidence-based argumentation. Interview results reveal that peer interaction, clarification questioning, familiar topics, lecturer guidance and feedback strongly support critical engagement. However, students face challenges such as limited background knowledge to the unfamiliar topics, low confidence, and difficulty interpreting complex information. Novelty/Originality of this study: This study offers insights into how Focus Group Discussion functions as a structured pedagogical strategy for developing critical thinking in EFL context. It not only provides an overview of students’ perceptions of the integration of critical thinking skills, particularly in terms of analyzing, evaluating multiple perspectives, and synthesizing ideas, but also through the use of mixed-methods approach, highlights specific components of Focus Group Discussion that support or hinder students’ critical engagement.